Effects of angiotensin type 1 receptor antagonists on Parkinson's disease progression : an exploratory study in the PPMI database - Udovin, Lucas Daniel (2021)
Fil: Udovin, Lucas Daniel. Universidad Abierta Interamericana. Centro de Altos Estudios en Ciencias Humanas y de la Salud; Argentina